(untitled) (Research, Society and Development, 2021)
Objective: To understand the expectations of the educational actions of 41 nurses in the nursing consultation for oncologic clients when they indicate a central venous catheter (CVC) for treatment. Method: Phenomenological qualitative research with 41 nurses indicating the use of CVC for treatment in oncologic clients of two units of a federal public hospital institution located in the city of Rio de Janeiro and specialized in oncology. Semi-structured interviews were used and the data were analyzed according to Alfred Schütz’s conceptions. Results: It was possible to identify the following categories: promoting comfort and safety for both the client and the professional; demystifying the use of the central venous catheter for the client; obtaining the client’s collaboration. Conclusion: The findings of the study revealed that the nurses aim to promote comfort and safety for the oncologic client throughout the treatment to prevent complications, even in cases where there is no prospect of cure. These professionals aim to sensitize the client to a possible change in behavior and that should be shared among the professionals of the multidisciplinary team of an interdisciplinary knowledge, the client, the family member in the search for the quality of appropriate and unique treatment.